HIV testing uptake and prevalence among hospitalized older adults in Togo: A cross-sectional study - (:unkn) unknown (My University, 2021)
OBJECTIVES: This study aimed to describe HIV testing uptake, as well as HIV prevalence and its associated factors among older adults aged ≥50 years in health facilities in Togo.METHODS: A cross-sectional study was carried out from February 2018 to June 2019 among hospitalized older adults aged ≥50 years in tertiary and secondary hospitals in Togo. HIV testing was performed according to the national algorithm. Socio-demographic data and HIV testing history were collected using a standardized questionnaire.RESULTS: A total of 619 patients (43.9% female) of median age 61 years, (IQR: 55-70) were recruited and offered HIV testing. Among them, 25.7% had never previously tested for HIV. In total, 91.6% (567/619) accepted HIV testing while 8.4% (52/619) refused to be tested. Of those who tested, forty patients were HIV positive, yielding a prevalence of 7.1%. Twenty-three patients (57.5%) were newly diagnosed with HIV infection. In multivariable analysis, two factors were associated with HIV infection: living alone (aOR = 5.83; 95%CI = [2.26-14.53]) and being \textbackslashtextless60 years (aOR = 3.12; 95%CI = [1.51-6.66]).CONCLUSION: The majority of older adults in this study accepted testing for HIV and almost three in five HIV positive older adults were newly diagnosed with HIV as a result of this testing. There is an urgent need to integrate older adults into responses to the HIV epidemic and to strengthen targeted prevention care and treatment in this population.
Keywords: African Research